2000
DOI: 10.1002/srin.200001329
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphorus on the ductility of high strength spring steels

Abstract: Phosphorus as a tramp element deteriorates the toughness and enhances the brittle fracture in high strength steels. Even very low bulk concentrations can cause severe enrichment on the prior austenite grain boundaries. This seriously restricts the applicability of highly demanded vehicle components. Three approaches were chosen to reduce the detrimental effect of phosphorus in quenched and tempered high strength CrV‐steels for high power leaf springs: Change in the chemistry (addition of boron for repelling ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Moreover, Augerelectron spectroscopy revealed that all variants with .9de£ .9def,2 < 800 DC produced a higher phosphorus enrichment at the grain boundaries than the optimum variant with .9def,2 = 800 DC which was finally applied for the following fatigue tests. that for a phosphorus concentration higher than approximately 0.02 % the ductility decreases with raising tempering temperature in the range &temp > 330 DC [7]. Moreover, for tempering temperatures in that range Z decreases with increasing phosphorus content above the threshold of P = 0.02 %, but maintains constant for P < 0.02 %.…”
mentioning
confidence: 86%
See 4 more Smart Citations
“…Moreover, Augerelectron spectroscopy revealed that all variants with .9de£ .9def,2 < 800 DC produced a higher phosphorus enrichment at the grain boundaries than the optimum variant with .9def,2 = 800 DC which was finally applied for the following fatigue tests. that for a phosphorus concentration higher than approximately 0.02 % the ductility decreases with raising tempering temperature in the range &temp > 330 DC [7]. Moreover, for tempering temperatures in that range Z decreases with increasing phosphorus content above the threshold of P = 0.02 %, but maintains constant for P < 0.02 %.…”
mentioning
confidence: 86%
“…This paper is focused on the possibilities to reduce the detrimental effect of phosphorus on the fatigue properties of CrY high strength steels for power leaf springs by optimizing process parameters and employing TMT. The results of the basic investigation on the static properties of phosphorus contaminated CrY steels are given in [7].…”
Section: Aims and Scopementioning
confidence: 99%
See 3 more Smart Citations